ANALISIS SIFAT MEKANIK PIPA CARBON STEEL GRADE A A106 DAN GRADE B A53 UNTUK PROSES PRODUKSI PADA KILANG LNG - Nofri, Media; Fardiansyah, Arif (Bina Teknika, 2018)
This study aims to determine the quality and mechanical properties of carbon steel pipes for the production process at a good liquefied Liquified Natural Gas and after 10 years of use. As a temporary repair reference on damaged pipe. The step is to compare the results of testing the mechanical properties and microstructure of both types of pipes. The parameters used are chemical composition, hardness, tensile strength, and micro structure of both types of pipes. Test results on a good pipe have an average hardness value of 90 HV whereas in the damaged pipe the average hardness value of 85.9 HV decreased by 4.1 HV. The tensile test on a good pipe value of 60kg / mm2 (588 MPa), on a damaged tube of tensile strength of 56 kg / mm2 (549 MPa), decreased 4 kg / mm2 (39 MPa). Good pipe microstructure test results consist of ferrite and pearlite structures while in the damaged pipe consisting of pearlite phase. From the results of the study concluded that the pipeline after the use for 10 years experienced a decrease in mechanical properties, namely: hardness and tensile strength. This is the result of thinning of the corrosion pipe wall thickness.